In situ delivery of synthetic preimplantation factor using aldehyde-modified hyaluronic acid hydrogel with immobilized complexes of chondroitin sulfate derivatives - Tutut Habibah; Andrea Exnerová; Kristina Nešporová; Una FitzGerald; Abhay Pandit; Marek Ingr; Martin Pravda; Vladimír Velebný (Carbohydrate Polymer Technologies and Applications)
Synthetic preimplantation factor (SPIF) is a promising therapeutic agent for chronic inflammatory diseases like Multiple Sclerosis (MS), but frequent systemic dosing limits patient adherence and therapy efficacy. This study presents an injectable drug delivery system (DDS) using 2 % (w/v) aldehyde-modified hyaluronic acid (HAOX) and chondroitin sulfate (CSOX) to deliver 100 µg of Fluorescein isothiocyanate-modified SPIF (FITC-SPIF). The DDS utilizes electrostatic interactions between the negatively charged sulfate groups of CSOX and the positively charged amino acids of FITC-SPIF for effective entrapment. Key properties were analyzed, including moderate gelation time (193 s), swelling profile (18 %), injectability (27 G needle) and an established relevant release profile (20 μg/daily ± 3) via anomalous diffusion. Increasing CSOX concentration reduced initial burst release by 38 % (0.5 % CSOX) to 78 % (1 % CSOX), extending release time (T50 %) from 50 h (0.5 % CSOX) to 88 h (1 % CSOX). Additionally, the release of FITC-SPIF enhanced TGF-β secretion in THP-1 macrophages, indicating preserved biological activity. These findings highlight the tunable release and mechanical properties achieved by adjusting the HAOX:CSOX ratio, strategically aligning the DDS for targeted MS symptom management. This system potentially simplifies SPIF delivery and enhances therapeutic efficacy.